Trophic State of The PLTA Koto Panjang Dam Kampar Regency Based on TSI (Trophic State Index) - Valentina Manurung; Madju Siagian; Asmika H Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrac Trophic State Index can be used to determine the trophic state of waters. The TSI was calculated based on chemical, biological and physical parameters and it is more representative for analyzing the trophical state of waters. To understand the trophic state of the PLTA Koto Panjang Reservoir, a research has been conducted in May 2018. There were four sampling stations, namely Station 1 (area with 100-150 floating cages) , Station 2 (area with 200-300 floating cages) and Station 3 (area with 946 floating cages). In each station, there were three sampling points, in the surface, in 2 Secchi depth, and in 4 Secchi depth. Sampling were conducted 3 times, once/week. Water quality parameter measured were total phosphorus, chlorophyll-a, transparency, temperature, pH, dissolved oxygen and free carbon dioxide. Trophic status was calculated based on Carlson’s Trophic State Index (TSI). The water quality parameter values were as follows: transparency 65.17-74.33 cm, total phosphorus 0.14 - 0.43 mg/L, chlorophyll-a 2.22 - 6.53 µg/L, depth 119.3 - 132.0 cm, temperature 27.7 - 31.7oC, pH 5.0, dissolved oxygen 3.04 - 6.81 mg/L and free carbon dioxide 09.39 - 26.93 mg/L. Trophic State Index value of the PLTA Koto Panjang Reservoir was 60.50 - 65.00, it indicates that the PLTA Koto Panjang water is in moderate eutrophic condition. Keywords: Carlson’sTrophic State Index, TSI, moderate eutrophic, and water quality